The problem of the natural activation of sphalerite during selective flotation - Azañero Ortiz, Ángel (2012)
The natural activation of sphalerite during flotation of lead is mainly related to the contamination of lead concentrate. The high content of zinc in the lead concentrate receives economic sanctions by higher refining costs, plus zinc content decreases in its flotation circuit. This research has been conducted on five samples of different minerals to identify the probable causes activation of natural sphalerite. The results indicate that the causes are intergrowths Mineralogical between lead and zinc, and the presence of soluble salts of Cu2 +. The ferrous ions and ferric Fe2 + Fe3 + did not show a significant effect on the activation of sphalerite.